2016
DOI: 10.1093/nar/gkw400
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing affects the subcellular localization of Drosha

Abstract: The RNase III enzyme Drosha is a key factor in microRNA (miRNA) biogenesis and as such indispensable for cellular homeostasis and developmental processes. Together with its co-factor DGCR8, it converts the primary transcript (pri-miRNA) into the precursor hairpin (pre-miRNA) in the nucleus. While the middle and the C-terminal domain are crucial for pri-miRNA processing and DGCR8 binding, the function of the N-terminus remains cryptic. Different studies have linked this region to the subcellular localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…Because GSK3b activity is regulated by various extracellular signals (Beurel et al, 2015), it is possible that serum starvation might cause an inhibition of GSK3b and mediate dephosphorylation of Ser 300/302 of Drosha, resulting in the accumulation in the cytoplasm. An alternatively spliced form of Drosha skipping exon 6, which encodes the putative nuclear localization signal, is reported to localize in both the cytoplasm and the nucleus (Dai et al, 2016;Link et al, 2016). However, the molecular size of cytoplasmic Drosha after serum starvation is equivalent to full-length Drosha (159 kDa) and indistinguishable from nuclear Drosha, thus it is unlikely that alternative splicing is involved in the change of nuclear/cytoplasmic ratio of Drosha upon serum starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Because GSK3b activity is regulated by various extracellular signals (Beurel et al, 2015), it is possible that serum starvation might cause an inhibition of GSK3b and mediate dephosphorylation of Ser 300/302 of Drosha, resulting in the accumulation in the cytoplasm. An alternatively spliced form of Drosha skipping exon 6, which encodes the putative nuclear localization signal, is reported to localize in both the cytoplasm and the nucleus (Dai et al, 2016;Link et al, 2016). However, the molecular size of cytoplasmic Drosha after serum starvation is equivalent to full-length Drosha (159 kDa) and indistinguishable from nuclear Drosha, thus it is unlikely that alternative splicing is involved in the change of nuclear/cytoplasmic ratio of Drosha upon serum starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Pri-miRNA increase may reflect an increase in mRNA resulting from the decrease in cleavage of the miRNA from exons in the Drosha KO cells. Finally, a recent study showed that the pri-miRNA processing efficiency is not correlated with the expression level of cytoplasmic Drosha isoform (52). We demonstrated that c-Drosha exists and is capable of processing pri-miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the middle and the C-terminal domain are important for pri-miRNA processing and DGCR8 binding, the activity of the N-terminus remains mysterious. Different investigations have linked this region to the subcellular localization of Drosha, stabilization, and response to tension [62]. The repression occurs solely in mature miRNAs and not in pri-miRNA transcripts, evidencing that the Drosha E1147K mutation affects processing of pri-miRNAs.…”
Section: Dicermentioning
confidence: 99%